The Phenomenon of Divorce during the Election Period in the Perspective of Islamic Law - Setiyawan, Deni; Tuasikal, Hadi; Karana, Hafidz Adhi (Jurnal Media Hukum, 2000)
This article delved into the perspectives of Islamic law about the divorce phenomena as it pertains to the election period. This phenomenon has been the subject of very little research about Islamic law. Legal anthropology brings an Islamic and conceptual studies perspective to this study technique. Consequently, this study aims to provide an Islamic perspective on these events and analyze them from a legal Islamic perspective. This article explained that ikhtilaf happened throughout the Islamic culture. During the election period, societal shifts inside the family led to the dissolution of the marriage. Since political opinions do not constitute nusyuz against the spouse, Muslims are free to have differing views on this matter. Only in religious issues is a woman bound to obey her husband. Thus, divorce is forbidden in Islam because of disparities in personal decisions. This study is expected to provide the groundwork for Islamic law and help families work through disagreements over political candidates during election period.